Photocatalytic Properties and Preparation of Nano-ZnO by Thermal Decomposition Based on ZIF-8. Issue 206 (23rd March 2020) - Shen, Weibin; Tang, Peisong; Cheng, Shun; Lv, Chunyan
Abstract: Using Zn(NO3 )2 ·2H2 O, 2-methylimidazole and CH3 COONa·3H2 O as main raw materials and methanol as solvent, ZIF-8 samples were prepared by hydrothermal reaction at 120 °C. And ZnO was obtained by calcination ZIF-8 in muffle furnace at 600 °C. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), diffuse reflectance spectroscopy (DRS) and thermos gravimetry-differential scanning calorimetry (TG-DSC). The photocatalytic activity of ZnO was investigated by methyl orange which was used as simulated sewage. The results show that the prepared ZnO is irregular, average grain size is about 80 nm, and the band gap width is 3.12 eV. Under UV-light, the degradation rate of 10 mg/L methyl orange is more than 70% in the presence of ZnO, while the degradation rate of methyl orange by commercial P25 is only 40%. The photocatalytic experiments show that the as-prepared ZnO has much higher photocatalytic activity than the commercial P25 photocatalyst. The ZnO is a kind of green photocatalyst which has a wide application prospect in the field of photocatalysis.